Creativity perception differences between males and females of undergraduate students: a pilot study - Nader, Habibollah; Abdullah, Rohani (2007)
This study was to investigate the difference in creativity of male and female students at Universities. The purpose was to investigate the difference between gender-role identity and creativity of students at Universities. The sample of 82 participants was females (N= 32) and males (N=50) Iranian students at Malaysia Universities. All students were given a Khatena - Torrance Creative Perception Inventory Test (KTCPI). This test is two parts: 1- creative something about myself (SAM) and 2- what kind of person are you? (WKOPAY). The aim of the present study was to investigate a comparison of creativity between Female Students (FS) and Male Students (MS) by the test of creativity. The sampling method in this study was the simple randomization method. Descriptive method focusing on Average, analysis of covariance and Variance, and inference of research using T-test between two groups of students were the two analysis methods used in this study. The (KTCPI) as a questioner test includes 100 items about quantitative the two parts of creative something about myself ( 50 items) and 2- what kind of person are you?( 50 items). In general, the results were not found significant between female and male students in relation to creativity. Further research is needed to investigate whether identify factors in the university environment which influence the development of female and male's creativity.